Formation of hierarchical In2S3–CdIn2S4 heterostructured nanotubes for efficient and stable visible light CO2 reduction - Wang, Sibo (2020)
We demonstrate rational design and fabrication of hierarchical In2S3-CdIn2S4 heterostructured nanotubes as efficient and stable photocatalysts for visible light CO2 reduction. The novel self-templated strategy, including sequential anion- and cation-exchange reactions, integrates two distinct sulfide semiconductors into hierarchical tubular hybrids with homogeneous interfacial contacts and ultrathin two-dimensional (2D) nanosheet subunits. Accordingly, the hierarchical heterostructured nanotubes facilitate separation and migration of photoinduced charge carriers, enhance the adsorption and concentration of CO2 molecules, and offer rich active sites for surface redox reactions. Benefiting from these structural and compositional features, the optimized hierarchical In2S3-CdIn2S4 nanotubes without employing noble metal cocatalysts in the catalytic system manifest remarkable performance for deoxygenative reduction of CO2 with high CO generation rate (825 μmol h–1 g–1) and outstanding stability under visible light irradiation.